Numerical Simulation of CTS/CdS Thin-Film Solar Cell - Sabina Rahaman; M. S. Sumathi; K. B. Jagannatha; K. V. Balvanth Gowda (Techniques and Innovation in Engineering Research Vol. 9, 2023)
In this book chapter, we have proposed new structure of Cu2SnS3 (CTS)/CdS thin-film solar cells using numerical modelling. Cell results are obtained by SCAP-1D solar simulator. Absorber layer thickness, and temperature is varied to optimise the CTS based cell performance. This study also examines the growth and recombination rates of CTS/CdS. Using this simulator, open circuit voltage, short circuit current density, fill factor and efficiency of the proposed cell is inspected. Open circuit voltages of 0.6V and fill factor of 72.89% was observed to enhance solar cell performance. CTS-based solar cell with CdS buffer layer showed a power conversion efficiency of 9.87% under optimum conditions.